Using the R = MC2 heuristic to assess whole-of-school physical activity implementation in elementary schools: a cross-sectional study - Derek W. Craig; Kevin Lanza; Christopher D. Pfledderer; Andjelka Pavlovic; Kempson Onadeko; Natalia I. Heredia; Jizyah Injil; Laura F. DeFina; Timothy J. Walker (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Schools are recommended to use a whole-of-school (WOS) approach to promote physical activity opportunities before, during, and after school. Yet, the barriers and facilitators to implementing a WOS approach successfully are not well understood. The R = MC2 heuristic, which defines readiness for implementation as a combination of an organization’s motivation and capacity to implement, can enhance our understanding of implementation in the school setting. This study examines associations between constructs from the R = MC2 heuristic and schools’ implementation of a WOS approach. Methods We conducted a secondary analysis of cross-sectional data from U.S. elementary schools participating in the NFL PLAY60 FitnessGram Project during the 2022–23 school year. From surveys administered to school staff, we created a WOS index (range = 0–12) comprising six physical activity practices: physical education, recess, before and after-school programs, classroom-based approaches, and active transport. We also assessed how six constructs from the R = MC2 heuristic (i.e., culture, implementation climate, leadership, priority, resources utilization, resource availability) impact physical activity implementation using a series of questions measured on a 5-point Likert scale. We used linear regression models to determine associations between R = MC2 constructs (independent variables) and WOS index scores (dependent variable), controlling for school-level characteristics (student enrollment, percentage of race/ethnicity and economically disadvantaged students served) and state-level clustering. Results The analytic sample consisted of 132 schools across 18 states. On average, school staff rated leadership (mean = 4.1, range = 1.5–5) and organizational culture (mean = 4.0, range = 2.25–5) the highest. The mean WOS index score was 6.1. Partially adjusted models indicated significant positive associations between each R = MC2 construct and WOS index scores. Fully adjusted regression models revealed priority (b = 0.88; p = 0.010; 95% CI = 0.19–1.56) and implementation climate (b = 0.69; p = 0.047; 95% CI = 0.07–1.32) were positively and significantly associated with WOS index scores. Conclusions Our study provides insights into key implementation constructs associated with providing school-based physical activity opportunities. These findings can support the development of resources and implementation strategies which, in turn, can help schools address implementation-related disparities. This will help schools improve the quality and accessibility of opportunities for physical activity provided to students across the United States.